Day‐case closure of ileostomy: feasible, safe and efficient. (September 2015) - Bhalla, A.; Peacock, O.; Tierney, G. M.; Tou, S.; Hurst, N. G.; Speake, W. J.; Williams, J. P.; Lund, J. N.
Abstract Aim Over 5000 loop ileostomy closures were performed in the UK in 2013 with a median inpatient stay of 5 days. Previously we have successfully implemented a 23‐h protocol for loop ileostomy closure which was modified for same‐day discharge. We present our early experience of day‐case loop ileostomy closure. Method A specific patient pathway for day‐case discharge following loop ileostomy closure was implemented with inclusion criteria to conform with British Association of Day Surgery guidelines. Exclusion criteria included postoperative chemoradiotherapy, multiple comorbidities and social care needs. Follow‐up consisted of telephone contact (24 and 72 h after discharge) and a routine outpatient appointment. Patients were provided with a 24‐h contact point in case of emergency. Results Fifteen (12 male) patients were enrolled of median age 67 (39–80) years. The median operating time was 41 (23–80) min. The indication for ileostomy formation was to cover a low anterior resection for adenocarcinoma (13), reversal of Hartmann's procedure (1) and functional bowel disorder (1). The median interval from the primary procedure to day‐case loop ileostomy closure was 8 (3–14) months. Every patient was discharged on the day of surgery. There were no complications related to the surgery and there was one readmission due to a urinary tract infection. The median length of follow‐up was 4 (2–16) months. Conclusion Our early experience shows that day‐case loop ileostomy closure is feasible, safe and efficient. This protocol will become standard within our institution for suitable patients, saving on average five inpatient bed days per patient.